Michael Vey : Storm of lightning - Evans, Richard Paul (Michael Vey, 2015)
"Michael and the rest of the Electroclan are facing their greatest crisis yet. The resistance movement has been compromised. The safe house has been destroyed. The voice is in hiding and they have no idea if their families are alive... or dead. What they do know is that the Elgen wont's stop until they've destroyed the Electroclan."--Dust jacket.